From Sight to Sip: The Role of Sensory Marketing in Local Coffee Shops - Dwiputri, Alodia Lastri; Syahputra; Pradana, Mahir (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2024)
Indonesia is a major coffee consumer, with around 25% enjoyed socially, enjoying coffee primarily while socializing with friends at cafes. However, the coffee shop industry faces intense competition due to market saturation. In the fiercely competitive coffee shop market, securing customer has emerged as a critical success factor. Customers are undeniably central to organizational success. The current research aims to analyze and empirically test these connections within the specific context of Bandung local coffee shops. A quantitative approach is employed through the distribution of questionnaires. The collected data will be analyzed using Smart PLS version 3.9. The results of this study can be used to inform strategies for implementing sensory marketing in coffee shop